Selected aspects of research methodology of a holistic educational environment in the light of the idea of sustainable development - Sandner, Jan (Studia Ecologiae et Bioethicae, 2009)
The concept of the balanced development idea caused a renewed view on the problems in the area of the research methodology in environmental education. The aforesaid viewis related to the necessity of implementing methods in which an appropriate place will be found for a holistic approach to occurring environmental processes. An approach enabling interdisciplinarity of this problem will finally find its solution also in a new teaching method. This forces a new quality of a perceptive view of the environment, however by no means severing from the accepted research methodology enforced in nature sciences. The devised and generated uniformed standardization of holistic environmental education methodology, philosophy of ecology and environmental ethics, should, as a result, impact not only the knowledge status on the said problem but also create quintessential basics in execution of research on the process of shaping the pro-ecology approach. The article also includes selected comments on the studies on estimation methods of the holistic nature science education, which were carried out in the 2006/2007 academic year at the Institute of Ecology and Bioethics of the UKSW (Cardinal Stefan Wyszyński University). The objective of the aforesaid studies, among others, was to work out new system solutions, which could be implemented into the academic teaching programs of the Environmental Protection study specialization. They should also become a reason for a discussion on research methodology for the final individual assignation of “Environmental Protection” studies in our country.